Makna Beauty Influencer Tasya Farasya di Akun Media Sosial Tiktok @tasyafarasya (Analisis Semiotika Roland Barthes) - Samsiah Nurhasanah; Rizqi Fitrianti; Arfian Suryasuciramdhan; Noerma Kurnia Fajarwati; Putri Handayani (STKIP Subang, 2025)
The role of influencers is increasingly prominent as parties capable of shaping audience perceptions and preferences for a product. Social media platforms like TikTok have become a strategic space for beauty influencers to build emotional closeness with their followers through engaging visual content. The research focused on audience meaning in three layers of meaning according to Roland Barthes's semiotics: denotative, connotative, and mythical. The method used was a qualitative approach with Barthes's semiotic analysis technique. Data were obtained through observation of one of the TikTok video content owned by @tasyafarasya. The analysis process was carried out by identifying visual and verbal signs, and tracing the meanings formed in the minds of the audience. The results show that at the denotative level, followers receive factual information related to the product, such as benefits and how to use it. At the connotative level, content is associated with lifestyle values, self-confidence, and representations of ideal women. Meanwhile, at the mythical level, beauty is interpreted as a symbol of social status and standards upheld in society. Tasya Farasya is considered successful in maintaining credibility through honesty, consistent content, and interactions that build trust. This strengthens his position as an influencer who not only shapes public opinion, but also significantly influences the purchasing decisions of his followers